2004
DOI: 10.1289/ehp.6779
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disinfection by-products and mutagenic activity on birth weight and gestational duration.

Abstract: Epidemiologic studies of disinfection by-products have traditionally focused on total trihalomethane (TTHM) concentration as a surrogate for maternal exposure during pregnancy. We used birth certificate data on 196,000 infants to examine the effect of third-trimester exposures on various indices of fetal development. We examined the effect of town-average concentrations of TTHM and additional exposure metrics in relation to mean birth weight, mean gestational age, small for gestational age (SGA) infancy, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 59 publications
6
128
3
1
Order By: Relevance
“…Wright et al (2004) and Jaakkola et al (2001) found a statistically significant decreased risk of pre-term delivery.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 87%
See 2 more Smart Citations
“…Wright et al (2004) and Jaakkola et al (2001) found a statistically significant decreased risk of pre-term delivery.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 87%
“…Hinckley et al (2005) found no association with THMs, but did for some specific HAAs. Studies on small for gestational age (SGA) and/or intrauterine growth retardation (IUGR) showed some more consistent results, and a good proportion of them have found statistically significant associations (Kramer et al 1992;Bove et al 1995;Wright et al 2003Wright et al , 2004, while some did not (Dodds et al 1999;Porter et al 2005;Yang et al 2007;Hoffman et al 2008b) (table 3). Aggazzotti et al (2004) found some effects with by-products of chlorine dioxide.…”
Section: (B) Reproductive Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…The sampling distribution from a previous study was used to assign the number of sampling locations per town (Wright et al, 2004). In all, 26 of the towns had two sampling sites, 47 of the towns had four sites, five towns had five sites, 16 towns had eight sites, and two towns each had six, eight and 10 sites, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Several reproductive epidemiologic studies of DBPs have used town average concentrations to estimate maternal exposure (Kramer et al, 1992;Bove et al, 1995;Savitz et al, 1995;Gallagher et al, 1998;Waller et al, 1998;Dodds et al, 1999;Klotz and Pyrch, 1999;Wright et al, 2003Wright et al, , 2004. Gallagher et al (1998) used geographic information system mapping and water hydraulic models to limit the impact of spatial variability on exposure misclassification.…”
Section: Introductionmentioning
confidence: 99%